Educational ideas of Dr. Antonio Isidro - Perez, Jose Ramirez 1945- (1973)
The aim of the study is to present the varied educational ideas of Dr. Antonio Isidro and their relevance to Philippine Education, and its accord with the provision specified in Section 5, Article XIV of the Philippine Constitution. Through this, the study intends that the advantageous ideas of Isidro may serve as guidelines in improving Philippine Education.
Thesis (M.A.)--University of the Philippines.
Keywords: Isidro, Antonio Santos -- 1901-.; Education -- Philippines